Analisis Resepsi Toxic Relationship dalam Film Pendek All Too Well Karya Taylor Swift - Shafira Ardhana Reswari; Wahidar, Tutut Ismi (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2021)
Toxic relationship is currently still a hot issue in society, both abroad and Indonesia. This issue is also widely raised in mass communication media, one of which is the short film named ‘All Too Well’ by Taylor Swift. This study aims to determine the position of dominant, negotiation, and opposition of the audiences to toxic relationship messages in Taylor Swift’s short film All Too Well. This study uses descriptive qualitative methods. Data were taken by interview, observation, and documentation techniques. Subject of this study are audiences of the short film, specifically 6 people selected through purposive technique and the object is audience’s interpretations of toxic relationship in Taylor Swift’s short film All Too Well. The data analysis technique used is reception analysis by Stuart Hall and the stages of analysis are data collection, data reduction, and drawing conclusions. The result showed that of the 6 informants who had received toxic relationship messages in this short film, 3 people received dominantly, 3 people more received negotiationally, and no one received full oppositionally to the short film. The differences between informants’ receptions were influenced by several factors such as their background of age, gender, and experience in life.